MENGENAL PEMBELAJARAN BIPA BERDASARKAN KEBUTUHAN BELAJAR PELAJAR ASING - Pratiwi, Adilah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia)
BIPA Learning is an Indonesian language learning program specifically designed to provide language learning services for foreign students. In BIPA learning, teaching materials and learning strategies are specifically designed according to the learning needs of foreign students. BIPA students are students as speakers of other languages who have diverse cultural backgrounds and learning goals. Cultural diversity and learning objectives of BIPA students have implications for the difficulty in choosing appropriate materials and strategies for implementing BIPA learning. The suitability of the choice of materials and strategies with the needs of BIPA students can motivate students and improve learning effectiveness. Therefore, an adequate understanding of student characteristics, learning needs, and teaching materials are important aspects that need to be mastered by BIPA teachers.